Effect of Different Human Papillomavirus Serological and DNA Criteria on Vaccine Efficacy Estimates - Lang Kuhs, Krystle A. (Oxford University Press, 2014)
Two trials of clinically approved human papillomavirus (HPV) vaccines, Females United to Unilaterally Reduce Endo/Ectocervical Disease (FUTURE I/II) and the Papilloma Trial Against Cancer in Young Adults (PATRICIA), reported a 22% difference in vaccine efficacy (VE) against cervical intraepithelial neoplasia grade 2 or worse in HPV-naïve subcohorts; however, serological testing methods and the HPV DNA criteria used to define HPV-unexposed women differed between the studies. We applied previously described methods to simulate these HPV-naïve subcohorts within the Costa Rica HPV16/18 Vaccine Trial and assessed how these criteria affect the estimation of VE. We applied 2 enzyme-linked immunosorbent assay (ELISA) thresholds for HPV16 and HPV18 seropositivity (8 and 7 ELISA units/mL, respectively, for PATRICIA; 54 and 65 ELISA units/mL, respectively, for FUTURE I/II (to approximate the competitive Luminex immunoassay)) and 2 criteria for HPV DNA positivity (12 oncogenic HPV types, plus HPV66 and 68/73 for PATRICIA; or plus HPV6 and 11 for FUTURE I/II). VE was computed in the 2 naïve subcohorts. Using the FUTURE I/II and PATRICIA criteria, VE estimates against cervical intraepithelial neoplasia grade 2 or worse, regardless of HPV type, were 69.0% (95% confidence interval: 40.3%, 84.9%) and 80.8% (95% confidence interval: 52.6%, 93.5%), respectively (P = 0.1). Although the application of FUTURE I/II criteria to our cohort resulted in the inclusion of more sexually experienced women, methodological differences did not fully explain the VE differences.